DIVERSITAS GASTROPODA DI SUNGAI SUKAMADE, TAMAN NASIONAL MERU BETIRI, JAWA TIMUR - Putut R. Purnama; Nimas W. Nastiti; Melia E. Agustin; Moch. Affandi (The East Java Biological Society, 2011)
Sukamade River is one of the main rivers in Meru Betiri National Park, especially at Sarongan Resort. Macrofauna benthic community in this river are in the protected areas that allegedly still original, and has not got the impact of human activity. Information about the diversity of gastropods class in Sukamade River in limited encourage to do research on the diversity of gastropods in this place. This research was conducted to determine the diversity of gastropods in Sukamade River. Gastropods samples taken at five stations those are in estuary, middle, and part of the river that closer to upstream river using surber-net and hand net. Surber-net used to take samples in watersheds zones and riparian zones using hand net. Samples were obtained, inserted the container that contains the fixative solution that formed by formalin 6% for preservation. Samples that have been preserved, and then sorted, identified and counted the number of individuals of each species, and data analysis. Data analysis, among others, to calculate the diversity index, evenness index, and dominance index in the Laboratory of Ecology Department of Biology, Airlangga University. From the analysis, obtained by the number of species found are 20 species that range from 8–14 species per station, the diversity index ranged from 1.860 to 0.795, evenness index ranged from 0.383 to 0.723 and the dominance index ranged from 0.223 to 0.659. Can be concluded that the diversity of gastropods in Sukamade River is at low-medium category.